PENGETAHUAN IBU MENYUSUI TENTANG ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS GUNUNG TUA - Melia Shintia Mutiara Pohan (Poltekkes Kemenkes Medan, 2022)
ASI or mother's milk is widely known to be able to provide appropriate nutrition for the needs of infants. WHO (World Health Organization) advises mothers around the world to give exclusive breastfeeding, namely giving only breast milk, without intake of other substances including water except vitamins; mineral; or medicine in the form of drops or syrup, during the first six months of the baby's life and continuing until the 2nd year of the baby's life. (Syafiq, 2017). Based on the state of the data above, the researcher wants to see an overview of breastfeeding mothers regarding exclusive breastfeeding in the Working Area of ??the Gunung Tua Health Center. Research Objectives To find out the knowledge of breastfeeding mothers about exclusive breastfeeding at the Gunung Tua Health Center. Type and Design This research is descriptive observational with a qualitative approach, conducted in the working area of ??the Gunung Tua Health Center to find out the knowledge of breastfeeding mothers about exclusive breastfeeding at the Gunung Tua Health Center. The population in this study were all breastfeeding mothers who had babies 0-6 months at Gunung Tua Health Center totaling 40 people. The total sample was all breastfeeding mothers who visited as many as 40 people. Based on these results, the knowledge of postpartum mothers showed that the majority had good knowledge of breastfeeding, totaling 22 people (55%). For attitudes, the research results obtained attitudes towards postpartum mothers which showed that the majority had good attitudes about breastfeeding, as many as 25 people (65.5%) , And based on the results of this study on the actions of postpartum mothers who showed the majority had sufficient action totaling 18 people (45%). Conclusions Based on the description of the results and discussion it can be concluded from the results of research conducted on 40 respondents in the Working Area of ??the Gunung Tua Health Center as a whole it can be it was concluded that postpartum mothers had good knowledge, namely 22 people (55%), good attitude of 25 people (62.5%) and those who had good enough actions were 18 people (45%).